Differentiation of the Hungarian food festival offer according to the thematic, spatial and temporal characteristics before the COVID-19 pandemic - Tóth, Bettina; Vida, György; Papp, Sándor; Nagy, Gyula (Turizam, 2022)
In our study, we analysed the pre-pandemic Hungarian gastro festival offer based on their topic, spatial and temporal characteristics, using media content analysis and advanced statistical methods. Based on the results, the Hungarian gastro festivals can be divided into several categories according to their theme and the emphasis of their theme. The examined festivals were mainly held in rural areas, most of them did not perform tourist functions, they can be defined as local, community events. According to the time characteristics, Hungarian festivals typically last for 1-2 days or are organized for 1-2 years. They are held primarily during the main tourist season, but some festival themes are also off-season. Based on our results, there is a correlation and difference between the theme, spatial features and temporality. The theme also influences the schedule, length and age of the festivals, while some themes can be linked to a city or countryside, and some themes are more relevant to tourism. Festivals are time-varying phenomena in terms of both number and territorial significance.
Keywords: food festival; food tourism; K-mean cluster; One-way ANOVA